EFFECT OF BIOTECHNOLOGICAL FERMENTATION WASTE KOMBUCHA ON THE GROWTH CHILI PEPPERS - Zivania Airila (SUAN PUBLISHER, 2024)
This study aims to evaluate the effects of kombucha biotechnology fermentation waste on the growth and yield of cayenne pepper (Capsicum frutescens) plants. As concerns about the environmental impacts of chemical fertilizers increase, the use of fermented organic waste is a promising alternative. Kombucha waste, rich in organic acids, vitamins, enzymes, and probiotic microorganisms, has the potential to be used as a biostimulant or liquid organic fertilizer. This study used an experimental method with a Completely Randomized Design (CRD) involving five treatments of kombucha waste concentration (0%, 25%, 50%, 75%, 100%) and four replications. The parameters observed included plant height, number of leaves, stem diameter, wet and dry plant weight, number of fruits per plant, and total fruit weight. Predictive results showed that the application of kombucha waste at an optimal concentration (predicted 50-75%) significantly increased the vegetative and generative growth parameters of cayenne pepper compared to the control. Kombucha waste has been proven to be a sustainable solution to increase cayenne pepper productivity and reduce industrial waste.